Hubungan Status Gizi dan Kepatuhan Konsumsi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Putri Ayu Kota Jambi - Karmila, Karmila; Sulastri, Sulastri; Haryati, Dwi; Susanti, Desy (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Maternal in Indonesia is still quite high caused by comparisons from anemia, such as bleeding. Anemia in pregnan women tends to be caused by a lack of iron intake and increased physiological needs during pregnancy. Anemia in pregnant women can be caused by a lack of iron micronutrients for fetal growth and distrupted eating patterns of pregnant women due to nausea during pregnancy. The purpose of this study was to determine the relationship between nutritional status and adherence to consumsing Fe tablets with the incidence of anemia in pregnant women at the Putri Ayu Health Center. The research method uses an analytic survey with a cross sectional approach. The research location was at the Putri Ayu Health Center, Jambi City. The population used is pregnant women who experience anemia in 2022 as many as 176 people, with the sampling technique using total sampling. Univariate and bivariate analyses were used to describe and see the relationship between nutritional status and sdherences to taking Fe tablets in pregnant women at the Putri Ayu Health Center, Jambi City, using chi-square test. Based on research that was conducted from 176 respondents, the majority of respondents experienced CED by 110 respondents (62.5%), and the mayority of respondent adhered to consuming Fe tablets by 114 respondents (64.8%). Most of the respondents with nutritional status of CED experienced moderate anemia as many as 66 respondents (37.5%), and most of the respondents with nutritional status not CED experienced mild anemia as many as 42 respondents (23.9%). Most of the respondents with adherence to consuming Fe tablets experienced mild anemia, 76 respondents (44.3%), and most of the respondents with non-adherence in consumsing Fe tablets experienced moderate anemia, 54 respondents (30.7%). Statistical results show that there is a relationship between nutritional status (p-value 0,002) and compliance in komsumsing Fe tablets (p-value 0,000) with the incidence of anemia in Putri Ayu Health Center, Jambi City. There is a relationship between nutritional status and adherence to consumsing Fe tablets with the incidence of anemia in pregnant women at the Putri Ayu Health Center, Jambi City. The nutritional status of pregnant women who are not CED through the upper arm circumference examination and adherence in consumsing Fe tablets can reduce the incidence of anemia in pregnant women. Keywords: Nutritional Status, Adherence to Consumption of Fe Tablets, Anemia ABSTRAK Kematian ibu di Indonesia masih cukup tinggi yang disebabkan oleh komplikasi dari kejadian anemia, seperti perdarahan. Anemia ibu hamil cenderung disebabkan oleh kurangnya asupan zat besi dan peningkatan kebutuhan fisiologis selama kehamilan. Anemia pada ibu hamil dapat disebabkan karena kekurangan mikronutrien zat besi untuk pertumbuhan janin dan pola makan ibu hamil yang terganggu akibat mual selama kehamilan. Tujuan penelitian ini adalah untuk mengetahui hubungan status gizi dan kepatuhan mengonsumsi tablet Fe dengan kejadian anemia pada ibu hamil di Puskesmas Putri Ayu. Metode penelitian menggunakan survey analitik dengan pendekatan cross sectional. Lokasi penelitian di Puskesmas Putri Ayu Kota Jambi. Populasi yang digunakan adalah ibu hamil yang mengalami anemia tahun 2022 sebanyak 176 orang, dengan teknik pengambilan sampel menggunakan total sampling. Analisis univariat dan bivariat digunakan untuk mendeskripsikan dan melihat hubungan antara status gizi dan kepatuhan mengonsumsi tablet Fe pada ibu hamil di Puskesmas Putri Ayu. Berdasarkan penelitian yang telah dilakukan dari 176 responden sebagian besar responden mengalami KEK sebesar 110 responden (62,5%), dan sebagian besar responden patuh mengonsumsi tablet Fe sebesar 114 responden (64,8%). Sebagian besar responden dengan status gizi KEK mengalami anemia sedang sebesar 66 responden (37,5%), dan sebagian besar responden dengan status gizi tidak KEK mengalami anemia ringan sebesar 42 responden (23,9%). Sebagian besar responden dengan kepatuhan mengonsumsi tablet Fe yang mengalami anemia ringan sebesar 76 responden (44,3%), dan sebagian besar responden dengan ketidakpatuhan mengonsumsi tablet Fe mengalami anemia sedang sebesar 54 responden (30,7%). Hasil statistic didapatkan ada hubungan status gizi (p-value 0,002) dan kepatuhan konsumsi tablet Fe (p-value 0,000) dengan kejadian anemia pada ibu hamil di Puskesmas Putri Ayu Kota Jambi. Terdapat hubungan status gizi dan kepatuhan mengonsumsi tablet Fe dengan kejadian anemia pada ibu hamil di Puskesmas Putri Ayu. Status gizi ibu hamil yang tidak KEK melalui pemeriksaan LiLA dan kepatuhan dalam mengonsumsi tablet Fe dapat menurunkan angka kejadian anemia pada ibu hamil Kata Kunci: Status Gizi, Kepatuhan Konsumsi Tablet Fe, Anemia